The origins of academic work on tourism: a European perspective - Butowski, Leszek (Turyzm/Tourism, 2020)
The purpose of this article is to fill in the gap in knowledge about early academic work on tourism which had developed first of all in Europe. The author has tried to achieve this aim by conducting a retrospective analysis of chronological and institutional-methodological aspects of the evolution of tourism studies. As a result, he has distinguished two aspects (each divided into two): 1) chronological: a period of precursors and a formal academic period; 2) methodological: research within one discipline and interdisciplinary research. The results enabled the author to formulate general conclusions for critical discussion. It primarily concerns the domination of the English language and the Anglo-American tradition in the literature which is the reason why the global picture of achievements in tourism studies is incomplete and thus imperfect. The accomplishments of smaller, yet well-established, “national schools” are often ignored and remain almost unknown internationally. The author hopes that the article will be an encouragement to undertake research on early tourism studies in individual countries and to publish its results internationally as this will broaden knowledge of the origins of academic work in tourism.